Pranggapan dalam Album DAYDREAM Karya Aimer (Kajian Pragmatik) - Lina Rosliana; Riana Anggun Rianti (Diponegoro University, 2020)
The purpose of this study to indentification form presupposition of Aimer songs in Daydream album and to describe the meaning of presupposition. The resources which used in this research are five song titled For Lonenly, Insane Dream, Kataomoi, Kowairo and Ninelie. This study use theory by Yule.The method of this study is use watch and note method for collection data, then use descriptive method for analysis data. In descriptive method will identify song lyrics by Aimer in album Daydream that contain presupposition and then analysis data with detail descriptive. The data presentation stage use informal method.The result of the study in song lyrics For Lonenly, Insane Dream, Kataomoi, Kowairo dan Ninelie are found that there are 63 data presupposition, such as 19 data of existence presupposition, 19 data of factual presupposition, 2 data of non-factual presupposition, 11 data of lexical presupposition, 7 data of structural presupposition and 5 data of counterfactual presupposition. The form of presupposition that often appears are existence presupposition total of 19 data and factual presupposition total of 19 data.